Major Organic Involvement in Women with Fabry Disease in Argentina - Fernando Perretta; Norberto Antongiovanni; Sebastián Jaurretche (The Scientific World Journal)
Fabry disease (FD) is an X-linked lysosomal storage disorder resulting from the deficiency or absence of the alpha galactosidase A enzyme. Organic involvement in men is well known, but in women it is controversial, partly due to the random X-chromosomes inactivation (Lyon hypothesis). The aim of this study was to describe the organic involvement in women at the time of FD diagnosis. A descriptive, cross-sectional and multicenter study was carried out. Thirty-five women with FD from three reference centers in Argentina were evaluated. The mean age of the whole group (n=35) was 26.6±16.9 years; 22 were adult (over 18) and 13 were paediatric patients. Enzymatic activity was performed in 29/35 patients, which was normal in 24/29 (82.8%). Seven different mutations of the GLA gene were found. The results showed urinary protein loss (45.7%) and decreased glomerular filtration rate (31.4%), mainly in adults. And also, cornea verticillata (56.5%), peripheral neuropathy (51.4%), cardiovascular manifestations (31.4%), hearing loss (20%), angiokeratomas (20%), central nervous system (17.1%), and gastrointestinal involvement (14.3%). Organic compromise in females with FD may be as severe as in men. This analysis has demonstrated a significant proportion of women with signs, symptoms, and major organic involvement at FD diagnosis.